2002
DOI: 10.1016/s1470-0328(02)01467-2
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transfer of citalopram, fluoxetine and their primary demethylated metabolites in isolated perfused human placenta

Abstract: Objective To investigate the transplacental transfer and the effects of protein binding on the transfer of citalopram, desmethylcitalopram, fluoxetine and desmethylfluoxetine in the isolated perfused human placenta model. Design Prospective observational study.Methods Fifteen term human placentas were obtained immediately after delivery with maternal consent and a 2-hour non-recirculating perfusion cycle of a single placental cotyledon was set up. Citalopram (1230 nmol/L) and desmethylcitalopram (600 nmol/L) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It was also found that infiltration across the placental barrier diminishes as the concentration of maternal HSA rises. Elsewhere, [84] it was found that HSA has a great influence on citalopram and fluoxetine placental transport, with its presence in the perfusion solute increased the degree of penetration; this effect was correlated with the affinity of the drugs to HSA: the passage of fluoxetine (PPB% = 94%) was significantly lower than that of citalopram (PPB% = 50%).…”
Section: The Placental Barriermentioning
confidence: 99%
“…It was also found that infiltration across the placental barrier diminishes as the concentration of maternal HSA rises. Elsewhere, [84] it was found that HSA has a great influence on citalopram and fluoxetine placental transport, with its presence in the perfusion solute increased the degree of penetration; this effect was correlated with the affinity of the drugs to HSA: the passage of fluoxetine (PPB% = 94%) was significantly lower than that of citalopram (PPB% = 50%).…”
Section: The Placental Barriermentioning
confidence: 99%
“…Antipyrine was transferred in a manner and amount comparable with earlier studies. 16,21,22 Transfer of saquinavir and antipyrine with different ATP concentrations Although the extent of saquinavir transfer was slightly smaller at an ATP concentration of 100 µM, the TPT of saquinavir, as measured by TPT AUC % (P = 0.66) or saquinavir concentration at 120 min (P = 0.67), did not vary between different ATP concentrations and the control perfusions (Figure 1, Table 2). In addition, no differences were found in the transfer of antipyrine (P = 0.71) or the transfer index (P = 0.63) between the range of ATP concentrations and the control perfusions (Table 2).…”
Section: Viability Of Placentasmentioning
confidence: 96%